how to train your dragon book 6 : a hero's guide to deadly dragons - Cowell, Cressida; Cressida Cowell (New York Hachette Book Group, 2007)
Hiccup faces his birthday with impending doom after Toothless eats a vital, sacred book, leading to potential banishment. To save his dragon, Hiccup must break into the Meathead Public Library to steal another copy, facing the Hairy Scary Librarian, 400 warriors, and Driller-Dragons.
English